PENERAPAN IPC TERMINAL OPERATING SYSTEM DAN LAYANAN PETI KEMAS PELABUHAN TANJUNG PRIOK - Johanes Kurniawan Liauw; Desta Utami; David Pandapotan (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
This study aimed at understanding the effect of the application of IPC Terminal Operating System (ITOS) on container receipt and / or expenditure services to and / or from the Nusantara II Field of Tanjung Priok Port. The problem of this research was whether the implementation of the IPC Terminal Operating System can make container acceptance and / or container services at the container terminal better. The analytical method used was simple regression, correlation coefficient, determinant coefficient, and t test. The results of statistical calculations obtain that the linear regression equation Y = 6.26 + 0.80X, explaining that the level of container acceptance and / or expenditure services can be predicted to be better if the implementation of ITOS increases better. The level of relations between the two variables is very strong and positive (r = 0.82). ITOS contribution to the level of strong container acceptance and / or expenditure services with a determinant coefficient value of 67.24%. ITOS has a significant effect on container revenue and / or expenditure services with a t count value (7.61) greater than t table (2.048).